Stages and areas of the use of IT tools supporting the management of IT projects - Pondel, Jolanta; Pondel, Maciej (Etapy i obszary wykorzystania narzędzi informatycznych wspomagających zarządzanie projektami informatycznymi, 2018)
Conducting informatic projects requires the application of modern solutions that streamline workflow. Current projects are becoming more complicated, during their implementation, large amounts of data and information are generated. In addition, in many external sources we can find data and information of the various forms and levels of detail. To get from this data a valuable knowledge, it is necessary to use new data analysis techniques and new technological solutions. The article sets out to present a dissertation of considerations for IT projects and the steps of IT project were highlighted with areas and IT tools that support their implementation. The aim of this article is to assess the current level of use of IT tools by the companies considered as leaders, at various stages of IT projects implementation. The authors also rated the intensity of IT tools usage in various areas of project execution. The paper includes results of research conducted, and can serve as a guideline for enterprises developing IT tools intended to streamline informatic projects. The contents of the dissertation are based on literature studies and empirical research
Management Sciences, 2018, vol. 23, no. 1, s. 45-57
Keywords: IT project; stages of the project; IT tools; management areas; projekt informatyczny; etapy projektu; narzędzia informatyczne; obszary zarządzania